Developing student questioning when problem solving: the role of sample student responses - Evans, Sheila; Swan, Malcolm (2015)
This paper describes intervention resources designed to provide opportunities for student self-regulation, with a particular focus on setting subgoals when problem solving. Each task includes a range of pre-written interrelated “sample student responses” that expose students to multiple perspectives on an unstructured non-routine problem. After students attempt the problem they are given the responses to collaboratively complete, critique and compare. We explore students’ capacity to adopt another person’s (the sample student’s) goals in order to complete a solution, and their capacity, through the use of comparison, to identify worthy criteria when critiquing the completed solutions. We then reflect on how we can make subsequent improvements to the resources.